18.45%‐Efficient Multi‐Crystalline Silicon Solar Cells with Novel Nanoscale Pseudo‐Pyramid Texture. (22nd August 2014) - Ye, Xiaoya; Zou, Shuai; Chen, Kexun; Li, Jianjiang; Huang, Jie; Cao, Fang; Wang, Xusheng; Zhang, Lingjun; Wang, Xue‐Feng; Shen, Mingrong; Su, Xiaodong
<x xml:space="preserve">Abstract</x> Silicon‐based cells could convert more solar energy to electrical energy if the cells could absorb more light. However, the nanostructured cells have demonstrated relatively low power conversion efficiency even when its reflection is very low; thus, they are still far from becoming real products of the photovoltaic industry. Here, nanoscale pseudo‐pyramid textured multi‐crystalline silicon (Pmc‐Si) solar cells, with the best efficiency of ≈18.45%, are fabricated by using a metal‐catalyzed chemical etching plus a post alkaline etching on an industrial production line. Such Pmc‐Si solar cells have showed similar light trapping ability as single crystalline silicon solar cells of micrometer pyramid texture, and the improved efficiency is mainly ascribed to its enhanced light absorption while the nanostructured surface still keeps acceptable passivation quality, that is, the short‐circuit current density has an increase of ≈300 mA cell–1, while the open‐circuit voltage has only a slight decrease of ≈1 mV. Further elevations of the efficiency are expected by optimizing both micrometer‐ and nanotextures, and exploring more effective passivation technique. More excitingly, the technique presented here has been verified in the production line for several batches as a real technique of low cost and high efficiency.